INTEGRASI NILAI-NILAI BUDAYA LOKAL DALAM PEMBELAJARAN MATEMATIKA UNTUK MENINGKATKAN MINAT BELAJAR SISWA - Siregar, Yasril Efendi Hamdy; Sagala, Pehulysa; Nasution, Amanda Syahri; Siregar, Nurhafni; Purba, Agnes Lucyana (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This study aims to increase students' interest in learning mathematics on the topic of exponential functions through the Culturally Responsive Teaching (CRT) approach by integrating Batak cultural values. This classroom action research was conducted in class X DKV 1 SMKN 10 Medan in the first semester of the 2024/2025 academic year. The research used the Kemmis and McTaggart model consisting of four stages: planning, action, observation, and reflection. The instruments used were learning interest questionnaires and observation sheets. Data were analyzed quantitatively and qualitatively. The results showed an increase in students' learning interest from 67.82% in the pre-cycle to 74.59% in cycle I, and further to 83.53% in cycle II. Learning integrated with local culture proved to make abstract material more contextual and meaningful, and increased student participation and enthusiasm. These findings support the effectiveness of the CRT approach in bridging abstract content with students' cultural experience while fostering 21st-century skills.